Exploring the components of professional ethics for residents of Iranian universities of medical sciences - Mojgan Mohammadimehr; Reza Ghanbari (Mashhad University of Medical Sciences, 2022)
Background: Professional ethics answers the ethical issues of various professions and has specific principles for it. The purpose of this study was to identify the Components of professional ethics for residents of Iranian universities of medical sciences.Methods: This qualitative study was conducted in Aja University of Medical Sciences. Semi-structured tools were used to collect data. The participants in this study were ethics experts in medical sciences who were selected by purposive sampling. Interviews with 19 experts led to data saturation. Data were analyzed using content analysis by Inductive approach. The Lincoln and Cuba criteria were used to evaluate the study data. Results: Based on the findings, 3 main themes including Organizational Ethics, Social Ethics, and Individual Ethics, and 12 sub-themes were obtained, as the components of professional ethics for residents of Iranian universities of medical sciences.Conclusion: It is recommended that educational officials in university, while paying more attention to professional ethics in the curriculum of residents, may use the results of this study in the development of professional ethics training programs for residents of medical sciences.